1988
DOI: 10.1111/j.2044-8279.1988.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Attitudes Toward School: Student Self‐reports and Teacher Perceptions

Abstract: This research compares teachers' perceptions of boys' and girls' attitudes to school with the students' own reports. Students (N = 2670) in Israeli elementary, middle and high school classes (N = 77) reported on their general satisfaction, commitment to schoolwork and relations with teachers and their teachers evaluated each student's attitudes for these domains. Results indicated that in most classes girls have more positive attitudes than boys and that teachers overestimate the magnitude of the difference. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 2 publications
1
10
0
4
Order By: Relevance
“…For example, some studies suggest that (some) boys show a lower motivation compared to girls in completing their homework and have low self-esteem and not very enthusiastic to continue their studies at a higher level (Darom & Rich, 1988;Warrington, Younger & Williams, 2000); and that these boys are able students who are particularly 'demotivated' (Van de Gaer et al 2006). Theorists such as Eccles et al (1993) and Roeser, Eccles & Sameroff (1998) have argued that schools that fail to meet the psychological needs of the adolescents would reduce the students' motivation and academic interests, and thus contribute to the reduction of student engagement and lower their academic performance in the transition from primary to secondary school.…”
Section: Gender In Educationmentioning
confidence: 96%
“…For example, some studies suggest that (some) boys show a lower motivation compared to girls in completing their homework and have low self-esteem and not very enthusiastic to continue their studies at a higher level (Darom & Rich, 1988;Warrington, Younger & Williams, 2000); and that these boys are able students who are particularly 'demotivated' (Van de Gaer et al 2006). Theorists such as Eccles et al (1993) and Roeser, Eccles & Sameroff (1998) have argued that schools that fail to meet the psychological needs of the adolescents would reduce the students' motivation and academic interests, and thus contribute to the reduction of student engagement and lower their academic performance in the transition from primary to secondary school.…”
Section: Gender In Educationmentioning
confidence: 96%
“…However, there have been studies on gender differences in the many components of student engagement (e.g., intrinsic motivation and persistence in school work) (Barber, 1996;Darom & Rich, 1988;Warrington, Younger, & Williams, 2000). As intrinsic motivation and persistence constitute the first two dimensions of student engagement, these findings will have implications regarding gender differences in student engagement.…”
Section: Gender Considerationsmentioning
confidence: 99%
“…As intrinsic motivation and persistence constitute the first two dimensions of student engagement, these findings will have implications regarding gender differences in student engagement. It has been reported that boys are less motivated than girls and spend less time doing homework and that boys have lower expectations of themselves and are less enthusiastic about continuing their studies (Barber, 1996;Cox, 2000;Darom & Rich, 1988;Hatzichristou & Hopf, 1996;Warrington et al, 2000). As for the cognitive dimension of student engagement, there is also evidence showing that girls are more likely than boys to plan, monitor, and regulate their cognitions and study activities (Ablard & Lipschultz, 1998;KenneyBenson, Pomerantz, Ryan, & Patrick, 2006;Patrick, Ryan, & Pintrich, 1999;Zimmerman & Martinez-Pons, 1990).…”
Section: Gender Considerationsmentioning
confidence: 99%
“…'Students in upper grades have less positive attitudes toward school when compared with students in lower ones' (Darom and Rich, 1988; see also Simpson and Oliver, 1985;Yager and Penick, 1986;Finson and Enochs, 1987;Midgley et al, 1989;Eccles et al, 1993). 'Students in upper grades have less positive attitudes toward school when compared with students in lower ones' (Darom and Rich, 1988; see also Simpson and Oliver, 1985;Yager and Penick, 1986;Finson and Enochs, 1987;Midgley et al, 1989;Eccles et al, 1993).…”
Section: Resultsmentioning
confidence: 99%